Exploration of the Relationship between Organization and Individual and its Influence on Employee Retention in Islamic Perspective - Aprilya, Nurul Wahida; Amrullah, Amrullah; Parmitasari, Rika Dwi Ayu; Syariati, Alim (Universitas Islam Internasional Darullughah Wadda'wah Bangil Pasuruan Jawa Timur, 2025)
High employee turnover is a major challenge for organizations, as it can impact productivity and long-term stability. In this context, an Islamic values-based approach offers a potential solution but is rarely addressed in research. This study aims to analyze the relationship between individuals and organizations in an Islamic perspective and identify factors that influence employee retention. This research method uses secondary data through literature review related to the individual-organization relationship, especially in relation to the concepts of Person-Organization Fit, Islamic Work Ethics (IWE), and Psychological Contract. The results show that individual and organizational relationships based on the values of honesty, trustworthiness, and fairness can strengthen employee loyalty and improve retention. On the other hand, conventional factors such as fair compensation, job satisfaction, and a positive work environment also proved to have a significant effect on employees' decision to remain in the organization. The Islamic perspective further emphasizes the importance of Islamic Organizational Commitment and the concept of The Celestial Management, which integrates spiritual and sharia values to create a work environment that supports well-being and long-term commitment. This research provides new insights into how Islamic values can be implemented in employee retention strategies to sustainably strengthen the individual-organization relationship.